Sprachen- und Wissenspolitik am Hofe Maximilians I. Die vernakularsprachigen Selbstzeugnisse als Instrument kaiserlichen Ambiguitätsmanagements - Rzehak, Kristina (Les langues des Habsbourg. Un empire plurilingue à l'époque moderne)
In European historiography, the period around 1500 is often referred to as a transitional period between the Middle Ages and the Early Modern period. During this period, the Habsburg Emperor Maximilian I reigned in the Holy Roman Empire and is often seen as a threshold per-son between these two epochs. This paper will examine the depiction of language and knowledge policy in Maximilian‘s literature. The following theses will be examined: By writing down his own life, the emperor performed identity work that was intended to have an effect on a specific audience. The choice of language for his self-testimonies was a deliberate one and aimed at addressing different groups of followers. Maximilian consciously used the potential of literature to depict ambiguities in order to make offers of identification to these different groups of followers. His language and knowledge policy is to be understood as part of Maximilian‘s ambiguity management, which was also applied in other areas. In this article, the specifics of Maximilian‘s ambiguity management in his language and knowledge policy are elaborated on the basis of an analysis of vernacular self-testimonies. The main goal of the depiction of language and knowledge policy is to achieve a balance between the different groups of followers. The emperor‘s self-portrayal proves to be ambiguous, but always results in an ideal. Despite the contradictions, the self-testimonies always portray Maximilian as a role model and ideal ruler and thus aim at appreciation and strengthening of loyalty by the recipients. Maximilian‘s striving for unambiguity in his claim to rule can be seen as the first indication of an overall development that will lead to a decrease in the still prevailing tolerance of ambiguity and a turning away from ambiguity management.